Maternal Behavior Determination in Infant Nutrition: A Study of Planned Behavior Theory in Stunting Prevention - Firdausi Ramadhani (Journal of Public Health Indonesian, 2025)
This study aims to analyze the determinants of maternal behavior in fulfilling toddler nutrition as part of stunting prevention efforts using the Theory of Planned Behavior (TPB). Effective stunting prevention requires a comprehensive understanding of psychosocial factors shaping maternal intention and behavior, as knowledge-based interventions alone are insufficient to produce consistent behavioral change. A systematic literature review (SLR) was conducted by synthesizing 29 peer-reviewed articles published between 2015 and 2025 from Scopus, Web of Science, PubMed, and Google Scholar. Thematic synthesis indicates that maternal attitudes toward balanced nutrition significantly influence feeding intentions, while subjective norms such as support from husbands, extended family, and health workers can either strengthen or weaken these intentions. The most decisive factor is perceived behavioral control, which reflects mothers’ ability to overcome structural barriers, including economic constraints, food access, time limitations, and the quality of health services. The three TPB components interact to shape actual feeding practices among mothers. This study concludes that stunting prevention interventions must integrate evidence-based education, strengthened family and community support, and improved access to health services to enhance maternal perceived behavioral control. These findings provide essential insights for developing behavior-focused nutrition interventions in Indonesia.